The Admissibility of Contractual Limitation of the Principle of Freedom of Work in a Negative Context - Sowińska-Olek, Monika (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The author analyzes the concept of freedom of work and the prohibition of forced and compulsory labor, with a focus on the negative aspect of freedom of work. Negative freedom of work is associated with the concept of labor based on the institution of a contract, i.e., the obligational relationship between the employee and the employer. As demonstrated by the legal provisions analyzed in this study, negative freedom of work is not absolute and may be subject to certain limitations. The aim of the article is to explore whether these limitations can also take the form of contractual restrictions. To address this question, the author examines the principle of freedom of contract and its limitations within the framework of labor law, and attempts to identify the boundaries of the parties' autonomy of will in the context of employment relationships.